Teacher Capacity Development Through Media Literacy In Special Needs School Pelita Hafiz, Bandung City - Zahrah Nabila Azka; Yusuf Hartawan; Fanny Oktaviani; Sharul Chandra (Jurnal Info Sains : Informatika dan Sains, 2023)
Along with the times, getting the information needed is getting easier, this is in line with technological developments that lead to the digital era as it is today. Through the Community Service Program (PKM) it is hoped that it will be able to provide partners with an understanding of the scope of media literacy. The concept of literacy is currently growing and is divided into several forms of literacy, one of which is digital literacy. Strengthening digital literacy for teachers is intended so that teachers have the ability to utilize digital media to increase teacher professionalism, especially for teachers who deal with students with special needs. Improving digital literacy skills can be done in various ways, one of which is through training activities. One of the school institutions with special needs that carry out digital literacy activities is the Pelita Hafizh Foundation Special School. The method implemented is through information dissemination (providing materials, discussions, direct practice) and technical guidance (Bimteks).